Staged surgical repair of severe pulmonary stenosis post radiofrequency ablation. Issue 9 (5th September 2022) - Murray, Lewis William; Gopal, Rakesh; Gimpel, Damian; Szpytma, Malgorzata (Maggie); Crouch, Gareth
Abstract: We present a case of a 68-year-old man who presents with worsening cough and dyspnoea 12 months after undergoing radiofrequency ablation therapy for atrial fibrillation. Investigation revealed complete occlusion of the left lower pulmonary vein and partial stenosis of the left upper pulmonary vein. He underwent a stage surgical resection with the first stage being a left lower lobectomy for the non-viable lobe followed by a repair of the left upper pulmonary vein via anastomosis with the left atrial appendage. This staged procedure yielded excellent results and avoided the need for a left-sided pneumonectomy.